Exposure to Di-(2-ethylhexyl) Phthalate During Perinatal Period Gender-Specifically Impairs the Dendritic Growth of Pyramidal Neurons in Rat Offspring - You, Mingdan; Dong, Jing; Fu, Yuanyuan; Cong, Zhangzhao; Fu, Hui; Wei, Lingling; Wang, Yi; Wang, Yuan; Chen, Jie (Frontiers in Neuroscience, 2018)
Di-(2-ethylhexyl) phthalate (DEHP), as a prevalent xenoestrogen endocrine disrupter, is omnipresent in the environment and commonly used in polyethylene plastic products. Although DEHP has potential adverse effects on multisystem organs, damage to the central nervous system is more significant. However, the consequences and mechanisms of DEHP exposure remain to be explored. The aim of this study was to investigate the effects and related mechanisms of maternal DEHP exposure on dendritic development of hippocampal pyramidal neurons in a rat model. Pregnant Wistar rats were intragastrically administrated either vehicle or DEHP (30, 300, and 750 mg/kg/d) from gestation day 0 to postnatal day (PN) 21. The dendritic length and complexity of dendritic arbors’ pattern in pyramidal neurons of the hippocampus were measured using Golgi–Cox staining and Sholl analysis. The expression of dendritic development-related proteins was detected using western blot and immunofluorescence staining. DEHP-treated male but not female pups showed an obvious decrease in the total length and branching numbers of basal dendrites on PN7, PN14, and PN21. The phosphorylation of MAP2c, stathmin, and JNK1 in the male pup hippocampus was significantly decreased in DEHP treatment groups compared to controls. However, protein expression alteration in the hippocampus of female offspring was not observed. In summary, our study indicated that DEHP has a gender-specific negative impact on the dendritic growth of CA1 pyramidal neurons in male offspring of a rat model of DEHP exposure. The adverse impact may be related to the dysregulation of phosphorylated and total MAP2c and stathmin mediated by JNK1.